2023
DOI: 10.1096/fj.202202048rr
|View full text |Cite
|
Sign up to set email alerts
|

CircHOMER1 inhibits porcine adipogenesis via the miR‐23b/SIRT1 axis

Abstract: Fat deposition is critical to pork quality. However, the mechanism of fat deposition remains to be elucidated. Circular RNAs (circRNAs) are ideal biomarkers and are involved in adipogenesis. Here, we investigated the effect and mechanism of circHOMER1 on porcine adipogenesis in vitro and in vivo. Western blotting, Oil red O staining, and HE staining were used to assess the function of circHOMER1 in adipogenesis. The results showed that circHOMER1 inhibited adipogenic differentiation of porcine preadipocytes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“… 43 Furthermore, previous studies conducted have indicated that circHOMER1 may inhibit adipogenic differentiation in porcine preadipocytes and C3H10T1/2 cells, thereby suppressing adipogenesis in mice through its interaction with SIRT1 via miR-23b. 44 , 45 This current study provides further confirmation that circMEF2C(2, 3) actively participates in the regulation of adipocyte proliferation and adipogenesis by functioning as a miR-383 and miR-671-3p sponge.…”
Section: Discussionsupporting
confidence: 75%
“… 43 Furthermore, previous studies conducted have indicated that circHOMER1 may inhibit adipogenic differentiation in porcine preadipocytes and C3H10T1/2 cells, thereby suppressing adipogenesis in mice through its interaction with SIRT1 via miR-23b. 44 , 45 This current study provides further confirmation that circMEF2C(2, 3) actively participates in the regulation of adipocyte proliferation and adipogenesis by functioning as a miR-383 and miR-671-3p sponge.…”
Section: Discussionsupporting
confidence: 75%
“…For example, the overexpression of miR-125a-5p promotes the proliferation but inhibits the differentiation of preadipocytes in pigs [ 17 ], and miR-125a-3p may regulate preadipocyte differentiation by targeting FSTL1 [ 18 ]. Furthermore, previous research has investigated the effect of circHOMER1 on porcine adipogenesis ex vivo and in vivo, demonstrating that circHOMER1 performed a depressant effect in adipogenesis by SIRT1 and miR-23b [ 19 ].…”
Section: Introductionmentioning
confidence: 99%